Blonanserin versus haloperidol in Japanese patients with schizophrenia: A phase 3, 8‐week, double‐blind, multicenter, randomized controlled study - Philip D. Harvey; Hiroshi Nakamura; Mitsukuni Murasaki (Wiley, 2019)
Abstract Objective This Japanese, multicenter, randomized, double‐blind trial, evaluating the efficacy and safety of blonanserin compared with haloperidol in patients with schizophrenia, was previously published by Murasaki in the Japanese language. In this article, we present the results of the trial based on full analysis dataset instead of per protocol dataset formerly reported and discuss the findings in light of the latest knowledge of pharmacological treatment for schizophrenia. Methods A total of 265 patients were randomized to receive blonanserin (8 to 24 mg/d) or haloperidol (4 to 12 mg/d) twice daily for 8 weeks. Efficacy assessments included the Clinical Global Impressions-Improvement (CGI‐I) and the Positive and Negative Syndrome Scale (PANSS). Results Blonanserin was not inferior to haloperidol with a margin of 10% with respect to the improvement rate on CGI‐I at end of study (60.5% vs 50.0%, P < 0.001). The decrease in the PANSS total score did not differ between the drugs (−10.3 vs −7.1). For the PANSS negative symptom score, the decrease was significantly greater with blonanserin than with haloperidol (P = 0.006). Blonanserin was well tolerated. The incidence of adverse events was similar for the two drugs. Extrapyramidal adverse events, sedation, hypotension, and prolactin increase were rarer with blonanserin than with haloperidol. No clinically important weight gain was observed. Conclusions Blonanserin is as effective as haloperidol for the treatment of schizophrenia. Blonanserin is more effective for negative symptoms with a lower risk of extrapyramidal symptoms compared with haloperidol.